Results of reference pricing and reimbursement discount rate schemes of Turkey - Kockaya, Guvenc; Atikeler, Kagan; Tuna, Esin; Kılıc, Pelin; Tanyeri, Pelin; Umman, Nurcan; Vural, İsmail Mert; Altun, Omer; Akbulat, Akif; Artiran, Guven; Simsek, Ercan; Gursoz, Hakkı; et al. (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
OBJECTIVES: General Directorate of Pharmaceuticals and Pharmacy (IEGM) is responsible for setting all prices for human medicinal products. The reference pricing system is used for setting these prices. Reference countries are reviewed annually and may be subject to certain alterations. There were 5 reference countries in 2009: Spain, Italy, Germany, France and Greece. The aim of this study is to show the distribution of reference countries which were used for reference pricing.METHODS: The price list of pharmaceuticals which was published by IEGM on 15.04.2011 was used for analysis. Distribution of reference countries and prices were evaluated.RESULTS: Prices of 6,251 generic and 3,703 original products were set according to the price list. 5,283 of generics and 3,306 of originals were in the positive list for reimbursement. Reference pricing was used for 2,352 generics and 2,281 originals. Prices of the remaining were set outside of reference pricing. 32 different countries were used for reference pricing. Italy was the most popular country for reference pricing. Even if it was not a reference country, Germany was used in some of the pharmaceuticals. The average reimbursement discount rate and price were 24.43% and 249 TL, respectively. There were no colerations between price and reimbursement discount rate, or reference country and reimbursement rate.CONCLUSION: It has been shown that Italy has the highest impact on the pricing of all pharmaceuticals in Turkey. Even if it was not a reference country, Germany showed to affect pharmaceuticals more than other countries which were also not used for reference pricing. Even if reimbursement discount rates are stated by the Social Security Institution (SGK), there are different discount rates for pharmaceuticals. The analysis stated that there were correlation between price, country and discount rates. This analysis is first for the literature. Further analysis is necessary in the light of price changes and newly launched pharmaceuticals.